Association of VEGF gene polymorphism with development and progression of diabetic retinopathy in India: a cross-sectional study - Jain, Kalpna; Chauhan, Suman; Yadav, Dinesh; Rizwan, Mohammad (International Journal of Research in Medical Sciences, 2025)
Background: Vascular endothelial growth factor (VEGF) polymorphism might be a useful predictive marker for the development and progression of diabetic retinopathy (DR). Methods: This observational cross-sectional study was done from December 2018 to December 2019. The study included 40 patients of DR and 20 healthy controls. A complete systemic and ocular examination was done including fundus examination, fundus photograph and OCT. The VEGF gene polymorphism of 936C/T, T(-1498)C, G(-1190)A, G(-1154)A and C(-634)G were studied. To study VEGF gene polymorphism the specific primer sequences were used in both forward and reverse directions. Genomic DNA was isolated from a blood sample using a genomic isolation kit and quantification of DNA was done at 260/280 nm on a spectrophotometer. PCR amplification was carried out on each primer. Results: 936C/T, T(-1498)C, G(-1190)A, G(-1154)A and C(-634)G VEGF gene polymorphism were found in 24 (60%), 34 (85%), 08 (20%), 19 (47.5%) and 21 (52.5%) cases respectively. 936C/T and T(-1498)C gene polymorphism were found in 08 (40%) and 05 (25%) controls respectively. 936C/T and G(-1190)A VEGF gene polymorphism was not statistically significant (p=0.234) (p=0.081) in study groups. T(-1498)C, G(-1154)A and C(-634)G VEGF gene polymorphism were significantly associated with the case and control groups. T(-1498)C, G(-1190)A, G(-1154)A and C(-634)G VEGF gene polymorphism was significantly associated with mild NPDR, moderate NPDR, severe NPDR, PDR and control group (p<.05). Conclusions: T(-1498)C, G(-1154)A and C(-634)G VEGF gene polymorphism was significantly associated with DR in the population of Western India. T(-1498)C and C(-634)G VEGF gene polymorphism was also associated with the severity of DR.